Design of a backpack dry leaves vacuum / Mohd Hazwan Mohamed Norli, Mohd Sapuwan Abu Bakar and Amirah Adam - Mohamed Norli, Mohd Hazwan; Abu Bakar, Mohd Sapuwan; Adam, Amirah (2020)
A backpack dry leaves vacuum is proposed to suck the dry leaves for outside cleaning services. It is functioned to reduce manpower, less noise and time saving instead of spending hours on end picking leaves for large areas. The backpack dry leaf vacuum consists of an aluminum funnel attached inside with garbage plastic, connected to a suction hose, filter, a pair of shoulder harness and battery pack. This backpack vacuum is very efficient and ergonomic in a matter of waste management because of the leaves and dirt will be collected directly into the garbage plastic.